Shelf-life Evaluation of Dehydrated Thai River Sprat (Clupeichthys aesarnensis) Product in Packaging with Nitrogen Gas using Accelerated Testing Method - Auyyuenyong, Ratchada; Boonthawee, Kitthawat; Wangdee, Kanitta (Journal of Food Technology, Siam University, 2023)
The objective of this work is to study shelf-life of dried fish Clupeichthys aesarnensis with a solar parabolic dome and to study the effect of packing conditions, packed in laminated aluminium foil bag (atmospheric condition/ nitrogen flush) on the shelf-life of the products using an Accelerated Shelf-life Test (ASLT) at 30, 40 and 50 °C, analyzed every 7 days for 8 weeks as a function of peroxide value. The result showed that increasing storage time is associated with increasing peroxide values for each storage temperature. The correlation between peroxide value and retention period was found that the peroxide value changes corresponded to the first-order kinetics with the highest R2 value. The peroxide value was 10 meq/kg as a criterion. For the shelf-life of product evaluated by Arrhenius equation, the shelf-life of the products stored in atmospheric condition packaging at 30, 40 and 50 °C were 115, 99 and 87 days (R2 = 0.999), respectively, while the shelf-life of products in nitrogen flush packaging were 137, 105 and 92 days (R2 = 0.978), respectively. The predicted shelf life of the product at 35°C was 151 days in nitrogen flush packaging. Results indicated that the nitrogen flush packing conditions could extend the shelf-life of dried fish products.